Cocoa Extract Provides Protection against 6-OHDA Toxicity in SH-SY5Y Dopaminergic Neurons by Targeting PERK - Vincenzo Vestuto; Giuseppina Amodio; Giacomo Pepe; Manuela Giovanna Basilicata; Raffaella Belvedere; Enza Napolitano; Daniela Guarnieri; Valentina Pagliara; Simona Paladino; Manuela Rodriquez; Alessia Bertamino; Pietro Campiglia; et al. (Biomedicines, 2022)
Parkinson’s disease (PD) represents one of the most common neurodegenerative disorders, characterized by a dopamine (DA) deficiency in striatal synapses and misfolded toxic α-synuclein aggregates with concomitant cytotoxicity. In this regard, the misfolded proteins accumulation in neurodegenerative disorders induces a remarkable perturbations of endoplasmic reticulum (ER) homeostasis leading to persistent ER stress, which in turn, effects protein synthesis, modification, and folding quality control. A large body of evidence suggests that natural products target the ER stress signaling pathway, exerting a potential action in cancers, diabetes, cardiovascular and neurodegenerative diseases. This study aims to assess the neuroprotective effect of cocoa extract and its purified fractions against a cellular model of Parkinson’s disease represented by 6-hydroxydopamine (6-OHDA)-induced SH-SY5Y human neuroblastoma. Our findings demonstrate, for the first time, the ability of cocoa to specifically targets PERK sensor, with significant antioxidant and antiapoptotic activities as both crude and fractioning extracts. In addition, cocoa also showed antiapoptotic properties in 3D cell model and a notable ability to inhibit the accumulation of α-synuclein in 6-OHDA-induced cells. Overall, these results indicate that cocoa exerts neuroprotective effects suggesting a novel possible strategy to prevent or, at least, mitigate neurodegenerative disorders, such as PD.